H-Coal: Conversion of Western Coals (7a3fb5cc-9d55-49e6-9160-0a768cefc2d7) - Clarence A. Johnson; Katherine C. Hellwig; Edwin S. Johanson; Harold H. Stotler; Ronald H. Wolk (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
The H-Coal process, an ebullated bed reactor system for converting coal to liquid fuel, is described. Results from long-duration continuous flow bench-scale operations with Wyoming Wyodak, Arizona Black Mesa, and Utah Kaiparowits Plateau coals are presented. Economic data on the conversion of these coals to liquid products are given. The potentials of the H-Coal process in regard to coal from western producers is stressed.